Detection of a cyclotron line in SXP 15.3 during its 2017 outburst. (3rd August 2018) - Maitra, C; Paul, B; Haberl, F; Vasilopoulos, G
ABSTRACT: We report the results of AstroSat and NuSTAR observations of the Be/X-ray binary pulsar SXP 15.3 in the Small Magellanic Cloud during its outburst in late 2017, when the source reached a luminosity level of ∼10 38 erg s −1, close to the Eddington limit. The unprecedented broad-band coverage of the source allowed us to perform timing and spectral analysis between 3 and 80 keV. The pulse profile exhibits a significant energy dependence, and morphs from a double-peaked profile to a single broad pulse at energies >15 keV. This can be explained by a spectral hardening during an intensity dip seen between the two peaks of the pulse profile. We detect a Cyclotron Resonance Scattering Feature at ∼5 keV in the X-ray spectrum, independent of the choice of the continuum model. This indicates a magnetic field strength of 6 × 10 11 G for the neutron star.